Analisis Peran Perangkat Desa dan Determinan Partisipasi Masyarakat dalam Pembayaran PBB-P2 di Desa Wonoboyo Kabupaten Temanggung - Nafisa Amalia Putri; Erlinda Nur Khasanah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Rural and Urban Land and Building Tax (PBB-P2) is a very important source of regional income. PBB-P2 payments have a role in supporting infrastructure development, improving community welfare, and financing social programs in the village. The purpose of this study was to examine the role of village officials and determinants of community participation in PBB-P2 payments in Wonoboyo Village, Temanggung Regency. Research method uses a qualitative descriptive approach through interviews. Interviews were conducted in January and February 2025 with village officials as parties who play a role in the socialization and management of PBB-P2 and taxpayers (local communities). The data obtained from the interviews were selected, summarized and focused on aspects relevant to the study, then presented in the form of narratives. The results of the study show that village officials have a very large role in collecting PBB-P2 in Wonoboyo Village. The determinants of tax sanctions have not been fully effective in increasing community compliance in paying PBB-P2. In addition, the level of taxpayer understanding of PBB-P2 in Wonoboyo Village varies widely. Most taxpayers are aware of their obligation to pay taxes, but do not understand in detail the purpose and benefits.